STRATEGI PENINGKATAN MUTU PENDIDIKAN PADA SEKOLAH DASAR NEGERI 22 BANDA ACEH - Suwardi Jamal (Jurnal Dedikasi Pendidikan, 2017)
This research aims to know about the Education Quality Improvement Strategy at State Primary School 22 Banda Aceh. The focus of research on policies, programs, strategies and discipline to the Principal, Superintendent of Schools, Teachers, Workers Filing and School Committee. Qualitative naturalistic approach used in this study with data collection tool interview, observation and documentation. Results of the study are: 1) Measures taken by the Principal and Supervisor equally mememilik desire to improve the quality of school education, but there is no cooperation. 2) Program in order to improve the quality of school education does not exist, but the teachers to deal with the learning process of their competence, prepare yourself Programme Implementation Plan (RPP). 3) Strategies to improve the quality of school education lies in the application of strict discipline, so that all teachers to teach discipline. Absorptive capacity of the subject matter is reached. 4) supporting factor in improving the quality of school education, the presence of high levels of teacher professionalism and strict discipline. Make teachers teach learners can be performed well, the quality of the learning process is created which indicate the passing standard obtain maximum (100%). Inhibiting factor in improving the quality of school education is not visible even though the school does not have a program. The implications of this research are: 1) Measures taken are not in line, do not affect the organization of education in school and will not impact on the quality of education. 2) school program does not exist, does not affect the implementation of school activities program, meaning that each element in carrying out tasks according to the program that are not integrated or not in one direction, has no effect on the graduation towards improving the quality of education. 3) strict discipline strategies make teachers in developing the learning process to be qualified, absorption of the subject matter is reached, so that these schools produce a graduation of 100% every year. 4) high teacher professionalism with high discipline, just as a contributing factor in improving the quality of school education. Do not have policies and programs, not as an inhibiting factor in improving the quality of school education..